Sound and Form Shifting of Loanwords from Japanese in the Indonesian Language - Khasanah, Umul; Husein, Ibnu (Technium Social Sciences Journal, 2022)
This study describes the process of shifting sounds and changes of the forms of loanwords from Japanese to the Indonesian language. This research’s type is descriptive qualitative with data in words identified as Japanese loanwords taken from KBBI Online. This research uses phonemics and morphologic approaches. After analysing all 48 loanwords data, it was found that 44 words had sound shifts, namely: 5 words of Assimilation, one word of Apheresis, 22 words of Apocope, 24 words of Syncope, one word of Monophthongisation, one word of Epenthesis, and one word of Paragoge. Furthermore, 4 data loanwords have changed the form of adding the prefix ’ber-’ as much as one word, and the prefix ’pe-’ as much as three words.